2022
DOI: 10.3389/fenvs.2022.1068379
|View full text |Cite
|
Sign up to set email alerts
|

Do renewable energy consumption and financial development contribute to environmental quality in MINT nations? Implications for sustainable development

Abstract: Maintaining a balance between the well-being of the economy and the environment has become a top priority for governments globally. In the contemporary age, world economies, particularly the emerging ones like MINT nations, highlight the need for eco-friendly economic expansion. The MINT nations are thriving economically but are having difficulty reducing their Ecological footprint (EF). This paper aimed to determine if factors such as population density, renewable energy, foreign direct investment, economic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…This result complies with the studies of 50 , 51 . However, this study contradicts 23 , 52 , who highlighted that with low-interest loans, financial development increases the spending power of the general public. This enables people to buy opulent goods like houses, cars, and air conditioners, all of which put a burden on the environment.…”
Section: Findings and Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This result complies with the studies of 50 , 51 . However, this study contradicts 23 , 52 , who highlighted that with low-interest loans, financial development increases the spending power of the general public. This enables people to buy opulent goods like houses, cars, and air conditioners, all of which put a burden on the environment.…”
Section: Findings and Discussioncontrasting
confidence: 82%
“…Besides, an insignificant linkage exists between financial development and emissions, suggesting that Malaysia financial section is still young. Moreover, the study of 23 for the MINT economies using data between 1990 and 2019 reported that an upsurge in financial development and economic expansion lessens the sustainability of the ecosystem while renewable energy and FDI inflows lessen ecological dilapidation. Furthermore, several studies in energy and environmental literature have reported significant various drivers of ecological quality such as economic growth, financial development, renewable energy, innovation, trade and globalization 24 26 .…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…As the negative consequences of ecological degradation, such as climate change and global warming, become more palpable, it raises environmental consciousness globally and compels nations to take action to lessen this devastation. 1 The inevitability of ecological deterioration due to economic expansion makes it difficult for policymakers to put environmental regulations into action rapidly. 2,3 As a result, economists focus their attention on the connection between macroeconomic and ecological indicators whereas policymakers keep searching for environmental measures with the least negative effects on economic indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between energy, the environment, and economic growth has received widespread attention in scientific research in recent years (Naeem et al, 2022;Duan et al, 2023a;Naeem et al, 2023;Ren et al, 2023), yet environmental sustainability remains a global issue. The development of renewable energy (Zhang and Wang, 2019;Adebayo et al, 2022), green technology innovation (Du et al, 2019;Habiba et al, 2022), and regulatory policy mechanisms (Abbas et al, 2021;Annamalaisamy and Vepur Jayaraman, 2023) contribute to reducing greenhouse gas emissions and supporting environmental sustainable development. Xu et al (2023) found that green technology innovation and environmental regulation are the most effective ways to achieve zero emissions.…”
Section: Introductionmentioning
confidence: 99%